Early detection of cognitive disturbances in mild cognitive impairment: a systematic review of observational studies. Issue 2 (6th December 2019) - Chehrehnegar, Negin; Nejati, Vahid; Shati, Mohsen; Rashedi, Vahid; Lotfi, Mohammadsajad; Adelirad, Fatemeh; Foroughan, Mahshid
Abstract : Mild cognitive impairment (MCI) is an intermediate state between normal cognition and early dementia and is not considered as a typical outcome of brain aging. It has been estimated that 10% to 20% of individuals above 65 years of age will be diagnosed as having MCI. The increased rate of dementia and the importance of early detection of its forerunners have encouraged researchers to focus on detecting MCI and modifiable risk factors with the hope of developing better ways of managing dementia and its consequences. The main aim of this study was to systematically review the related literature concerning the cognitive changes in the spectrum of cognitive aging to cognitive impairment. Articles included in this review were identified through searching the databases of PubMed, Psych Info, Embase, ProQuest, and Scopus. Many domains like verbal memory, language, executive function, visual memory, attentional skills, and working memory showed acceptable predictive power. Testing subdomains such as executive function, speed of processing, working memory and semantic language are critical and others may indicate some suggestions for further clinical deteriorations in normal individuals. Although various cognitive instruments have been used for evaluation of impaired cognitive domains, it remains challenging to select the most appropriate ones having high‐level accuracy and their related cognitive subdomains. It also revealed that none of the identified cognitive domains solely fulfilled the criteria for MCI screening; in clinical settings, multiple neuropsychological batteries may be used for one single cognitive domain, while longitudinal studies prefer the use of at least two cognitive measures for each domain to improve accuracy and research settings might focus on only a single neuropsychological test. However, along with episodic memory, testing for amnestic MCI, executive function could increase the chance of early detection of MCI. Executive control has been found to deteriorate the earliest in MCI patients.